COMMUNICATION STRATEGY IN THE ESTABLISHMENT OF CHARACTER EDUCATION ON STUDENTS OF SAIM Elementary School (SEKOLAH ALAM INSAN MULIA) SURABAYA IN ONLINE LEARNING OF THE COVID 19 PANDEMIC - Alamsyah, Muhammad Zufar Mimbar (The Commercium, 2022)
The covid 19 pandemic has turned the world of education into online learning. SAIM schools that carry the concept of integrated, joyful and cooperative learning where learning should be maximized when face to face, then must be familiar with online learning. This study aims to determine the application of communication strategies by Alam Insan Mulia (SAIM) Surabaya school teachers in applying the concepts of integrated, joyful and cooperative learning by using qualitative descriptive research methods and case studies. The results of this study indicate that SAIM which has 3 learning concepts, integrated, joyful and cooperative learning where the three concepts are used during face-to-face learning are also used during online learning. It’s just that the 3 concepts have differences in the process. These differences lead to the methods and media used by modifying and demanding teachers to be more creative and communicative in the practice of 3 learning concepts. In addition, the role of parents is also greater because learning cannot be carried out at school but at home, so that more intense communication is needed between parents and teachers for the development of their students.